Exploring Characteristic of Women Leadership in Socio-Religious Organization The Catholic Woman of The Republic Of Indonesia South Kalimantan Region - Melania Melania; Anthonius Junianto Karsudjono; Amiartuti Kusmaningtyas; Tri Ratnawati (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2021)
Leadership often associated with certain age, gender, or race that causes someone considered not good enough to be promoted in a particular position, even in this era it is still prevents women from becoming leaders, even though they have a huge opportunity to be able to practice being a leader. So there is a difficulty of finding cadres who